Marketing Strategy in Play: Questioning to Create Difference - Hill, Mark E (Business Expert, 2012)
When marketers have a clear focus on the true task confronting them and are effective at it, then competition becomes a nonissue. What is the true task that alleviates the need for competition? Thinking about thinking is the process that challenges how we think about marketing and competition. The ideas presented in “Marketing Strategy in Play : Questioning to Create Difference” explain marketing thinking, how to cultivate it, and ultimately the ways in which marketplace differences are created. Rather than providing some formulaic series of marketing steps, processes, and models based on someone else’s thinking, the focus here is on developing the practitioner’s thinking. This provocative perspective requires deeper reading and thinking about many of the familiar notions found in marketing. For example, why compete? The book is written for serious practitioners interested in breaking from the familiar ways of doing things and in fi nding unique approaches to stimulate their own thinking effectively for any organization, large or small. What will the reader take away from “Marketing Strategy in Play : Questioning to Create Difference”? First, the book examines difference: how marketing differences are created and how to be more effective at the process of difference creation that can benefi t an organization; as such, difference is explored at a level deep enough to understand its nature. Second, it explains that marketing thinking is predicated upon a type of questioning from which marketing differences (e.g., answers) originate. Third, marketing is redefi ned as a way of thinking rather than as a discipline or function. Fourth, the relationships among thinking, questioning, curiosity, and difference are revealed for the purpose of developing ways in which the marketer can become more effective at the game of marketing. Fifth, there are many new and different notions offered in the book that can be understood and used by practitioners in their own situations. Finally, questioning techniques are discussed for strategy development purposes.